ANALISIS IMPLEMENTASI PRINSIP AKUNTABILITAS DALAM PENGELOLAAN DANA DESA (STUDI DI KECAMATAN SIDOMULYO, KABUPATEN LAMPUNG SELATAN) - Yudastio (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to analyze the implementation of the principles of accountability, transparency, and community participation in the management of Village Funds in Sidomulyo Subdistrict, South Lampung Regency. The background of this study is the importance of applying good governance principles to village financial management so that Village Funds truly benefit community welfare. The research employed a mixed-methods approach with an embedded concurrent strategy, in which quantitative data were obtained through questionnaires and qualitative data were collected through semi-structured interviews with the same respondents. The findings indicate that the implementation of accountability and transparency principles has been reasonably good at the planning and administrative stages, although delays in reporting and limited public access to information are still observed. Meanwhile, community participation has begun to manifest in the planning and implementation stages but remains low at the monitoring and evaluation stages. These findings emphasize the need to improve the capacity of village officials, strengthen socialization mechanisms, and develop more inclusive communication strategies to ensure the optimal implementation of accountability, transparency, and community participation principles